Pendekatan partisipatif dalam pemetaan batas kampung dan potensi bahaya (Studi kasus: Kampung Cungkeng, Teluk Betung Selatan, Bandar Lampung) - Nana Putri Yanto; Sahid Sahid; Dessy Reza Saputri (Regional Development Information Center, Universitas Sebelas Maret, 2026)
A participatory approach comes as a strategy for regional management and disaster mitigation. This study examined the application of participatory approach in mapping village boundaries and potential hazards in Kampung Cungkeng, Teluk Betung Selatan District, Bandar Lampung. The area faces several challenges such as territorial management, kampung boundary disputes, and disaster risks such as tsunamis, floods, and coastal abrasion. The study aimed to engage local communities in boundary mapping and hazard identification as a basis for regional development and disaster preparedness. A qualitative descriptive method was employed, using data collected through Focus Group Discussions (FGDs), in-depth interviews, and field observations. Global Positioning System (GPS) devices and ArcGIS software was used in mapping activities to produce accurate digital maps. The results indicate that participatory mapping provided clear delineation of village boundaries and identified key hazard potentials, particularly tsunamis and flash floods. This approach enhanced community awareness and capacity in understanding disaster risks. These findings highlight the importance of participatory mapping in supporting sustainable coastal regional development and disaster risk reduction.